Comparison of the Accuracy of CBCT and MDCT Images in Measuring the Thickness of the Posterior Footplate of the Middle Ear in Iranian - Sharifi Shooshtari , Sanaz; Saki , Nader; Roozbahani , Zohreh; Farahmandfar , Kowsar; Bagheri , Nila (Galen Medical Journal, 2025)
Background: Advancements in radiological imaging have transitioned from two-dimensional radiography to three-dimensional cone beam computed tomography (CBCT), offering high spatial resolution with reduced radiation doses compared to multidetector computed tomography (MDCT). While MDCT remains the standard for detailed visualization of bony structures like the ossicular chain, its higher radiation exposure is a concern. This study compares the accuracy of high-resolution (HR) and low-resolution (LR) CBCT with MDCT in measuring the thickness of the posterior footplate of the middle ear to identify a reliable, low-radiation alternative. Materials and Methods: Twelve adult human temporal bones from Imam Khomeini Hospital’s ENT Department were imaged using HR-CBCT, LR-CBCT (Jundishapur Dental School), and MDCT (Siemens Sensation 64-slice). Standardized imaging protocols ensured reproducibility, with measurements of posterior footplate thickness conducted in axial, coronal, and sagittal planes by two blinded radiologists. Data were analyzed using SPSS v23, with inter-modality agreement assessed via Kappa coefficient and differences evaluated with the McNemar test. Results: Mean posterior footplate thickness was 2.38 mm (HR-CBCT), 2.37 mm (LR-CBCT), and 2.23 mm (MDCT), with no significant differences (p > 0.05). HR-CBCT and LR-CBCT showed comparable accuracy to MDCT. Conclusion: CBCT, particularly HR-CBCT, offers a reliable, lower-radiation alternative to MDCT for otologic imaging, maintaining high resolution for middle ear assessments.